Identification of the novel HLA‐DRB1*11:308 allele in a Greek individual. (30th November 2022) - Zamanakou, Maria; Vatsiou, Sophia; Batsaki, Panagiota; Fortis, Sotirios P.; Germenis, Anastasios E.
Abstract : We report here the identification by next‐generation sequencing of a novel HLA allele, DRB1*11:308, in a Greek individual as a part of a research project investigating diagnostic and prognostic biomarkers in head and neck cancer (BIOKARETRA).